Biodegradable thermal adhesive coating agent composition and method of preparation thereof

By using components such as thermoplastic starch and natural resin in hot melt adhesives, combined with specific manufacturing methods, the problems of existing packaging materials being unenvironmentally friendly and poorly bonded during hot melt bonding are solved, and efficient bonding and biodegradability to various substrates are achieved.

JP2025069035AActive Publication Date: 2025-04-30EVERCHEMTECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023215411
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-17
Filing Date
2023-12-21
Publication Date
2025-04-30
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

Existing packaging materials are not environmentally friendly during hot melt bonding and are not easy to bond well with various substrates, and the viscosity changes of the adhesive during storage lead to difficult application.

Method used

A biodegradable hot melt adhesive consisting of thermoplastic starch (TPS), pH adjuster, viscosity stabilizer, first and second solvents, and natural resins is used to ensure viscosity stability and strength consistency through a specific manufacturing method.

Benefits of technology

It has achieved efficient hot melt bonding to various substrates such as paper and plastic, and has good biodegradability and environmental protection, stable viscosity and water resistance, and is suitable for the production of a variety of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069035000001_ABST
    Figure 2025069035000001_ABST
Patent Text Reader

Abstract

To provide a biodegradable thermal adhesive coating agent composition, which is biodegradable and has superior properties and to provide a method of preparation thereof.SOLUTION: The present invention relates to a biodegradable thermal adhesive coating agent composition and a method of preparation thereof, and more specifically, it relates to a biodegradable thermal adhesive coating agent composition, which is biodegradable in order to be environment-friendly, excellent in its adhesion to substrates of various materials, such as paper, plastic, etc., stable in water resistance and viscosity change, and suitable for a production process using thermal adhesion, as well as a method of preparation thereof.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biodegradable coating composition for thermal adhesion and a method for producing the same, and more particularly to a biodegradable coating composition for thermal adhesion that is biodegradable and environmentally friendly, has excellent adhesion to various substrates such as paper and plastic, is stable in water resistance and viscosity change, and is suitable for thermal adhesion production processes, and a method for producing the same.

[0002] The biodegradable thermal bonding composition of the present invention does not require adhesives or laminating equipment, and therefore reduces production costs and environmental load, making it possible to utilize the composition in a variety of fields. [Background technology]

[0003] Currently, various instant foods or disposable packaged foods are widely used, and food packaging materials are also widely used accordingly. Such food packaging materials must have appropriate barrier properties against moisture and air to maintain the freshness and taste of food, excellent adhesion to substrates, be environmentally friendly in consideration of the environment and health, and be highly compatible with the human body. In addition to food packaging materials, various packaging materials such as pharmaceutical packaging materials and Ringer's solution bags are also required to have water resistance, barrier properties, biodegradability, environmental friendliness, etc. However, conventional packaging materials are used as interleaving paper for films such as PE and PP plastics as thermal adhesive materials, which are not biodegradable and therefore have the problem of being unfriendly to the environment.

[0004] In response to the above-mentioned problems, starch-based materials have been developed as alternative materials. Although these materials are excellent in terms of recyclability and environmental friendliness, they have been pointed out as having a problem that, over time after starch gelatinization, hydrogen bonds between starch chains increase, causing the viscosity of the reaction product to increase, making it impossible to distribute the finished product.

[0005] Therefore, there is a demand for compositions that can be applied to various substrates such as paper, metal, glass, and plastic, that are environmentally friendly, harmless to the human body, and have stable thermal adhesion, water resistance, and viscosity. Summary of the Invention [Problem to be solved by the invention]

[0006] In order to solve the above-mentioned problems of the prior art, the present invention aims to provide a coating composition for thermal adhesion that is biodegradable and has excellent physical properties, and a method for producing the same. In particular, the present invention provides a biodegradable coating composition for thermal adhesion that can be applied to various types of substrates, has stable viscosity without aging over time, and can maintain a certain adhesive strength, and a method for producing the same. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides a biodegradable coating composition for thermal adhesion, comprising thermoplastic starch (TPS), a pH adjuster, a viscosity stabilizer, a first solvent, a second solvent, and a natural resin.

[0008] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: (a) adding a pH adjuster to a first solvent; (b) adding a thermoplastic starch to the (a) solution; (c) increasing the temperature of the (b) solution; (d) adding a viscosity stabilizer to the heated (c) solution and reacting it; (e) cooling the (d) solution; (f) adding a second solvent to the cooled solution; (g) adding a natural resin to the (f) solution; (h) stirring the (g) solution and then recovering the final solution; The present invention relates to a method for producing a biodegradable thermal adhesive coating composition comprising the steps of: Effect of the Invention

[0009] The biodegradable coating composition for thermal adhesion of the present invention has the advantages of being excellent in thermal adhesion strength, excellent in durability, adjustable in viscosity, and applicable to various substrates such as paper, plastic, etc. Therefore, it is expected that the composition can be used not only as a food packaging material but also as a packaging material in various fields. [Brief description of the drawings]

[0010] [Figure 1] 1 is a photograph showing the liquid stability of the composition of Example 13. [Diagram 2] FIG. 2(a) is a photograph showing the composition of Comparative Example 1, and FIG. 2(b) is a photograph showing the liquid stability of Comparative Example 2. [Diagram 3] 1 is a photograph showing the liquid stability of Comparative Example 3. [Figure 4] FIG. 4(a) is a photograph showing the water absorbency of the composition of Example 13, and FIG. 4(b) is a photograph showing the water absorbency of the composition of Comparative Example 11. [Diagram 5] 1 is a photograph showing the result of peeling off the coated paper after the composition of Example 4 was thermally adhered. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in more detail with reference to the following specific examples. The following examples are intended to describe preferred embodiments of the present invention, and the scope of the present invention should not be construed as being limited by the details described in the following examples.

[0012] In the present invention, "%" means % by weight.

[0013] "Biodegradable" generally refers to a material that is broken down by the action of naturally occurring microorganisms, such as bacteria, fungi, and algae, heat, moisture from the environment, or other environmental factors.

[0014] "Thermoplastic starch" means starch obtained by treating it with a plasticizer.

[0015] The present invention relates to a biodegradable thermal adhesive coating composition comprising a thermoplastic starch (TPS), a pH adjuster, a viscosity stabilizer, a first solvent, a second solvent, and a natural resin.

[0016] In one embodiment, the composition comprises 7 to 25 wt % thermoplastic starch (TPS), 1 to 5 wt % pH adjuster, 0.08 to 1.0 wt % viscosity stabilizer, 3 to 20 wt % second solvent, 3 to 35 wt % natural resin, and the remainder being the first solvent.

[0017] In one embodiment, the thermoplastic starch is added in an amount of 7 to 25% by weight of the coating composition. When the content is within the above range, it is advantageous in terms of realizing thermal adhesive strength and productivity. If the content of the thermoplastic starch is less than 7% by weight, the amount of solvent becomes relatively large, and it takes more time to dry the solvent in the process, which is disadvantageous in terms of productivity, and if it exceeds 25% by weight, the viscosity becomes very high, which makes it difficult to apply the process.

[0018] In the present invention, in order to provide the starch with adhesiveness and coating stability, acrylic resin, silane hydrolyzate, urethane resin, polyolefin resin, biodegradable resin, etc. may be mixed or combined. The biodegradable resin may include at least one of PLA (polylactic acid), PCL (polycaprolactone), PPC (polypropylene carbonate), PGA (polyglycolic acid), PBAT (polybutylene adipate terephthalate), PBS (polybutylene succinate), PHA (polyhydroxyalkanoate), TPS (thermoplastic starch), and PEC (polyethylene carbonate). By combining a hard biodegradable resin (e.g., PLA) with a soft biodegradable resin (e.g., PCL, PPC), various coating materials can be produced, and biodegradable films with various physical properties can be formed using the coating materials. For example, by mixing a hard biodegradable resin and a soft biodegradable resin in a solution, a biodegradable film having excellent physical properties such as barrier properties, coating properties, mechanical strength, etc. Furthermore, paper coated with the biodegradable film can be used for various purposes and is environmentally friendly.

[0019] The pH adjuster is not particularly limited as long as it is an alkaline substance that promotes gelatinization of starch and inhibits retrogradation, and any known material can be selected and used. In one embodiment, the pH adjuster may be any one selected from inorganic alkaline compounds such as sodium hydroxide, potassium hydroxide, calcium hydroxide, and sodium carbonate. The organic alkaline compound includes a primary amine, a secondary amine, a tertiary amine, or a mixture thereof, and the primary amine is any one or more selected from the group consisting of methylamine, methanolamine, ethylamine, ethanolamine, propylamine, 3-amino-1-propanol, isopropylamine, monoisopropanolamine, tert-butylamine, butylamine, hexylamine, dodecylamine, cyclohexylamine, ethylenediamine, and hexamethylenediamine, and the secondary amine is any one or more selected from the group consisting of dimethylamine, diethylamine, diethanolamine, dipropylamine, N-ethylmethylamine, N-methylpropylamine, 3-(methylamino)-1-propanol, N-isopropylmethylamine, dibutylamine, diisopropyl ... and the tertiary amine is at least one selected from the group consisting of trimethylamine, trimethanolamine, triethylamine, triethanolamine, dimethylethanolamine, N,N-dimethylpropylamine, N,N-dimethylbutylamine, 3-dimethylamino-1-propanol, N,N-dimethyldodecylamine, N,N-dimethyloctadecylamine, tripentylamine, N,N-dimethylcyclohexylamine, 3-(dimethylamino)benzyl alcohol, and N,N,N',N'-tetramethyl-1,4-butanediamine.

[0020] In particular, sodium hydroxide can be used. In one embodiment, the pH adjuster can be used in the range of 1 to 5% by weight. If it is added in an amount of less than 1% by weight, the gelatinization of starch is minimal, and the aging inhibition effect is reduced, and if it is added in an amount of more than 5% by weight, the coating agent contains an excessive hydrophilic substance, and the water resistance of the coating film after coating is poor.

[0021] Viscosity stabilizers are bulky single molecules that are located in the starch chains to prevent hydrogen bonds between starch chains, suppress the viscosity increase phenomenon, and allow the viscosity to be adjusted to the desired level depending on the type. In addition, because they have a high carbon number and few functional groups, they can also contribute to improving water resistance.

[0022] In one embodiment, the viscosity stabilizer may be any one or more selected from the group consisting of lecithin, lysolecithin, glycerin fatty acid ester, sucrose fatty acid ester, propylene glycol fatty acid ester, isolated whey protein (9410 WPI), concentrated whey protein (8000 WPC), soy protein isolate (SPI), rice protein isolate (RPI), oat protein isolate (OPI), pea protein isolate (PPI), casein, sodium caseinate, corn protein, gelatin, wheat protein, dextrin, carrageenan, Tween 80, Tween 20, and cellulose. In one embodiment, the viscosity stabilizer can be used in the range of 0.08 to 1.0% by weight. If it is added in an amount less than 0.08% by weight, there is no effect of preventing viscosity increase, and if it is added in an amount more than 1.0% by weight, a problem of reduced thermal adhesiveness occurs. In one embodiment, it is preferably used in the range of 0.1 to 0.5% by weight.

[0023] The first solvent is not limited to, but may be, for example, one or more of water, distilled water, and purified water.

[0024] The second solvent may be an alcohol having 1 to 6 carbon atoms, and may be, for example, one or more selected from the group consisting of alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-butanol, tert-butanol, n-amyl alcohol, isoamyl alcohol, 2-amyl alcohol, tert-amyl alcohol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, cyclohexanol, and mixtures thereof.

[0025] The second solvent improves coatability and the production rate of coated paper, and inhibits enzyme action to prevent spoilage when using natural-based materials.

[0026] In one embodiment, the second solvent is used in an amount of 3 to 20% by weight. When the amount is less than 3% by weight, there is no effect of improving the coating property and productivity, and when the amount is more than 20% by weight, there is a possibility that starch will precipitate. In one embodiment, the amount is preferably 3 to 10% by weight.

[0027] In one embodiment, the composition of the present invention may further include a natural resin, and preferably, shellac may be added. Shellac is a type of animal resin, and is produced by refining or bleaching the yellow gum secreted by lac bugs, and is usually used as a paint or finishing agent. In the present invention, it is used as a coating agent for the purpose of improving water resistance and antibacterial properties. In one embodiment, shellac is used at 3 to 35% by weight. When added at less than 3% by weight, there is no effect of improving water resistance and antibacterial properties, and when added at more than 35% by weight, shock with starch occurs, and the mixture of starch and shellac precipitates in a mass, which may make it difficult to use as a coating agent. In one embodiment, it is preferably 15 to 30% by weight.

[0028] In addition to the above components, other additives may be added to the composition of the present invention, such as dispersing aids, melt stabilizers, processing stabilizers, heat stabilizers, light stabilizers, antioxidants, heat aging stabilizers, brighteners, antiblocking agents, binders, lubricants, water-soluble polymers, fillers, etc. Dispersing aids may be used, for example, to aid in the formation of a uniform dispersion and to retard or prevent separation into component phases. Similarly, dispersing aids may improve the water dispersibility of the coating composition.

[0029] Furthermore, the present invention relates to a method for producing a (a) adding a pH adjuster to a first solvent; (b) adding a thermoplastic starch to the (a) solution; (c) increasing the temperature of the (b) solution; (d) adding a viscosity stabilizer to the heated (c) solution and reacting it; (e) cooling the (d) solution; (f) adding a second solvent to the cooled solution; (g) adding a natural resin to the (f) solution; (h) stirring the (g) solution and then recovering the final solution; The present invention provides a method for producing a biodegradable thermal adhesive coating composition, comprising the steps of:

[0030] In the step (a), a pH adjuster can be added to the first solvent while stirring with a mechanical stirrer, and then in the step (b), thermoplastic starch can be added, and the reaction mixture can be heated to 60 to 90°C in the step (c), but is not limited thereto.

[0031] Then, in step (d), the viscosity stabilizer can be added to the reaction solution while slowly stirring, and the reaction can be allowed to proceed. The viscosity stabilizer can be added according to the content range of the above-mentioned type. Then, the reaction can be allowed to proceed for 1 to 4 hours, but is not limited thereto.

[0032] In step (e), the reacted solution can be cooled to room temperature.

[0033] In step (f), the second solvent is slowly added to the cooled solution while stirring, and then, in step (g), a natural resin is added to the solution. Then, in step (h), the solution (g) is stirred, and the final solution can be recovered. The reaction can be carried out for 10 to 30 minutes, but is not necessarily limited to this.

[0034] In one embodiment, the natural resin is shellac.

[0035] In one embodiment, the prepared biodegradable thermal adhesive coating composition can be further dispersed using ultrasonic waves, a high-pressure disperser, or a homogenizer to disperse the composition uniformly. Preferably, the composition can be dispersed using a high-pressure dispersion method.

[0036] In one embodiment, further physical properties can be adjusted through a heating and / or pressure step, and residual solvent can be removed by a drying step.

[0037] The biodegradable coating composition for thermal adhesion can be provided on a substrate at a thickness of 0.1 μm to 90 μm. The thicker the thickness, the higher the thermal adhesion strength, and the thinner the thickness, the lower the manufacturing cost.

[0038] The substrate to which the biodegradable thermal adhesive coating composition is applied may be paper, plastic, metal, or the like, and may include a functional layer between the substrate and the coating layer to provide additional physical properties. For example, a primer layer or an oxygen barrier layer may be selectively laminated, or a primer layer and an oxygen barrier layer may be laminated simultaneously. The primer layer or the oxygen barrier layer may further include a step of applying the primer layer or the oxygen barrier layer to a thickness of 1 μm to 10 μm. When a coating liquid is coated on a film coated (surface-treated) with, for example, a urethane primer, the primer improves adhesion, and the coating layer coated on the substrate film does not easily peel off. In addition, the film may be further subjected to a surface treatment such as plasma or corona to improve adhesion.

[0039] In one embodiment, the step of providing the coating composition for biodegradable thermal adhesion on the substrate may be performed by coating the coating composition for biodegradable thermal adhesion on the substrate, for example, spray coating, spin coating, dip coating, gravure coating, microgravure coating, die coating, comma coating, knife coating, direct coating, bar coating, etc., but is not limited thereto.

[0040] The coated composition can be dried on the substrate by evaporating the solvent using a hot air dryer at a temperature of 60 to 150°C for 1 to 5 minutes, preferably at 100°C for 2 to 3 minutes, though this is not limited thereto.

[0041] In the following the following examples illustrate the invention without limiting its scope.

[0042] [Example 1] As the first solvent, 88.4g (68wt%) of distilled water was stirred at 300 rpm using a mechanical stirrer, and 1.5g (1.15wt%) of 1N NaOH was added. Then, 10g (7.69wt%) of thermoplastic starch was added, and the reactant was heated to 80°C. When the temperature reached 80°C, the mixture was stirred at 500 rpm, 0.1g (0.08wt%) of lecithin was slowly added, and the mixture was reacted at 80°C for 1 hour, and then cooled. 100g of the reactant at room temperature was stirred at 1,000 rpm using a mechanical stirrer, and 10g (7.69wt%) of ethanol was slowly added as the second solvent. After adding ethanol, 20g (15.38wt%) of shellac was added 10 minutes later, and the reactant was collected after stirring for 20 minutes. The final composition was uniformly dispersed using a high pressure disperser (1000 bar, 3 passes) to a particle size of about 100 nm.

[0043] [Examples 2 to 25] A coating composition was prepared in the same manner as in Example 1, except that the components and contents were changed as shown in Table 1 below.

[0044] [Comparative Examples 1 to 11] In the process of Example 1, coating agent compositions were produced in the same manner as in Comparative Examples 1 to 11 in Table 1, except that the components and contents were changed.

[0045] [Table 1]

[0046] [Comparative Example 12] The same process as in Example 1 was followed to prepare the composition, except that the high pressure dispersion process was not carried out after the composition was recovered.

[0047] [Experimental Example 1] Liquid stability measurement The compositions of the examples and comparative examples were stored under normal temperature and humidity conditions for 30 days, and then visually observed for stability. Figures 1(a) and 1(b) are photographs showing the liquid stability of the composition of Example 1. Figures 2(a) and 2(b) are photographs showing the liquid stability of the composition of Comparative Example 1 and Comparative Example 2, respectively. Figure 3 is a photograph showing the liquid stability of the composition of Comparative Example 12, which was not subjected to a dispersion process.

[0048] The composition of Example 1 was kept in a homogeneous and stable state, whereas the compositions of Comparative Examples 1 and 2 were spoiled or gelled, respectively, making them difficult to use as coating compositions. Comparative Example 12 was unsuitable as a coating composition due to the occurrence of thickening.

[0049] [Experimental Example 2] Viscosity measurement The viscosity of the compositions prepared in the Examples and Comparative Examples was measured (spindle: No. 06, rpm: 100 rpm) using a viscometer (DV2TRV, manufactured by Brookfield) under normal temperature and humidity conditions (20±5° C., 55±5%). The results are shown in Table 2.

[0050] [Experimental Example 3] Moisture absorption measurement After the base paper was firmly attached to the glass plate, about 1 to 2.5 g of the coating composition prepared from the composition of the above Examples and Comparative Examples was dropped onto the top of the base paper, and the composition was applied to a uniform thickness on the base paper using a bar coater. The film on which the composition was applied was dried at 100°C for 2 minutes using a hot air dryer to produce coated paper. The prepared coated paper was then subjected to a 100 cm 2Distilled water was poured onto the circular test piece, which was then left for 60 seconds, and the moisture absorbency was evaluated by calculating the weight after the test minus the weight before the test. The results are shown in Table 2. FIG. 4(a) is a photograph showing the moisture absorbency of the composition of Example 1, and FIG. 4(b) is a photograph showing the moisture absorbency of the composition of Comparative Example 1. The composition of Example 1 was stable with no visible change, while the composition of Comparative Example 1 was observed to absorb moisture and cause the paper to wrinkle.

[0051] [Experimental Example 4] Measurement of thermal adhesive strength The coating agent prepared in Experimental Example 3 was applied to a thermal gradient tester (QM930D, manufactured by Qmesys) with the lower plate of the heating plate set at 60°C and the upper plate at 150°C, and two sheets of coated paper were placed between the plates facing the coating layer and pressure was applied for 1 second to thermally bond them. The thermally bonded coated paper was then cut to a size of 10 mm wide and 100 mm long (thermal bonding area: 10 mm wide and 25 mm long) to prepare a sample, and the adhesive strength was measured using a universal material testing machine (LS1, manufactured by Lloyd). The results are shown in Table 2.

[0052] [Table 2]

[0053] As shown in Table 2, the compositions of the Examples generally exhibited properties effective as adhesive compositions, whereas the compositions of the Comparative Examples spoiled or gelled and could not be applied. Generally, the compositions of Examples 5 to 8, 10, 13, 14, 20, and 22 to 25 were evaluated as being preferable in terms of viscosity, water absorption, and adhesive strength. Example 6 had a slightly increased viscosity, Example 8 was somewhat slow to dry, Example 11 had high water absorption, Examples 15 and 19 caused shock, and Example 21 had low thermal adhesive strength.

[0054] Furthermore, in Experimental Example 3, coated paper to which the composition of Example 1 was applied was thermally bonded and then peeled off, and the results are shown in Fig. 5. It was found that the sealability was so excellent that the paper broke when peeled off.

Claims

1. A biodegradable thermal adhesive coating composition comprising thermoplastic starch (TPS), a pH adjuster, a viscosity stabilizer, a first solvent, a second solvent, and a natural resin.

2. 2. The composition of claim 1, wherein the composition consists of 7-25% by weight of thermoplastic starch, 1-5% by weight of a pH adjuster, 0.08-1% by weight of a viscosity stabilizer, 3-20% by weight of a second solvent, 3-35% by weight of a natural resin, and the balance being the first solvent.

3. The composition of claim 2 wherein said natural resin is shellac.

4. 2. The composition of claim 1, wherein the pH adjuster is selected from at least one of sodium hydroxide, potassium hydroxide, triethylamine, ethylenediamine, and dimethylethanolamine (DMEA).

5. The viscosity stabilizer may be lecithin, lysolecithin, glycerin fatty acid ester, sucrose fatty acid ester, propylene glycol fatty acid ester, whey protein isolate (9410 WPI), whey protein concentrate (8000 WPC), soy protein isolate (SPI), rice protein isolate (RPI), oat protein isolate (OPI), pea protein isolate (PPI), casein, sodium caseinate (Sodium caseinate), or the like. The composition according to claim 1, wherein any one or more selected from the group consisting of corn protein, gelatin, wheat protein, dextrin, carrageenan, Tween 80, Tween 20, and cellulose is used.

6. The composition of claim 1 , wherein the first solvent is one or more of water, distilled water, and purified water.

7. 2. The composition of claim 1, wherein the second solvent is at least one selected from the group consisting of ethanol, methanol, isopropyl alcohol, and mixtures thereof.

8. A packaging material comprising the composition according to any one of claims 1 to 7.

9. (a) adding a pH adjuster to a first solvent; (b) adding a thermoplastic starch to the (a) solution; (c) increasing the temperature of the (b) solution; (d) adding a viscosity stabilizer to the heated (c) solution and reacting it; (e) cooling the (d) solution; and (f) adding a second solvent to the cooled solution; (g) adding a natural resin to the (f) solution; (h) stirring the (g) solution and then recovering the final solution; A method for producing a decomposable thermal adhesive coating composition comprising the steps of:

10. The method according to claim 9, wherein the natural resin is shellac.

11. The method according to claim 9, wherein in the step (c), the temperature is raised to a range of 60 to 90°C.

12. The method according to claim 9, wherein in the step (d), after adding the viscosity stabilizer, the reaction is carried out for a period of 1 to 4 hours.

13. The method according to claim 10, wherein after the shellac is added, the reaction is carried out with stirring for 10 to 30 minutes.

14. The method of claim 9, further comprising the step of dispersing the recovered composition by performing a high pressure dispersion step after the step (g).

Citation Information

Patent Citations

  • Biodegradable processed materials consisting essentially of or based on thermoplastic starch

    JP2000515566A

  • Resin composition, resin composition solution and resin composition dispersion

    JP2003073501A

  • Method for preparing a plasticized starch-based thermoplastic composition and the resulting composition

    JP2011511121A

  • Fiber structure and production apparatus of fiber structure

    JP2022052117A

  • Biodegradable coating composition, method for producing the same, and biodegradable article using the same

    JP2024527832A